Assessment of the compositions and components for obtaining foam-glass-crystalline materials from aluminosilicate initial materials; Glass and Ceramics; Vol. 66, N 3-4 - Kazmina O. V. Olga Viktorovna (2009, 2009)
The compositions suitable for obtaining foam-glass-crystalline materials from aluminosilicate initial materials (for the example of zeolite and greenstone) by means of a dual-stage technology at temperatures not exceeding 900°C are examined. The assessment criteria for the initial materials and compositions of the glass granulate are determined. It is shown that under the established conditions aluminosilicate initial material makes it possible to obtain foam-glass-crystalline material with density 250-350 kg/m3 and compression strength up to 2 MPa